Multiple environmental antigens may trigger autoimmunity in psoriasis through T-cell receptor polyspecificity - Tatsushi Ishimoto; Yukiyasu Arakawa; Secil Vural; Julia Stöhr; Sigrid Vollmer; Adrian Galinski; Katherina Siewert; Geraldine Rühl; Yuri Poluektov; Marc Delcommenne; Orsolya Horvath; Mengwen He; et al. (Frontiers in Immunology, 2024)
IntroductionPsoriasis is a T-cell mediated autoimmune skin disease. HLA-C*06:02 is the main psoriasis-specific risk gene. Using a Vα3S1/Vβ13S1 T-cell receptor (TCR) from a lesional psoriatic CD8+ T-cell clone we had discovered that, as an underlying pathomechanism, HLA-C*06:02 mediates an autoimmune response against melanocytes in psoriasis, and we had identified an epitope from ADAMTS-like protein 5 (ADAMTSL5) as a melanocyte autoantigen. The conditions activating the psoriatic autoimmune response in genetically predisposed individuals throughout life remain incompletely understood. Here, we aimed to identify environmental antigens that might trigger autoimmunity in psoriasis because of TCR polyspecificity.MethodsWe screened databases with the peptide recognition motif of the Vα3S1/Vβ13S1 TCR for environmental proteins containing peptides activating this TCR. We investigated the immunogenicity of these peptides for psoriasis patients and healthy controls by lymphocyte stimulation experiments and peptide-loaded HLA-C*06:02 tetramers.ResultsWe identified peptides from wheat, Saccharomyces cerevisiae, microbiota, tobacco, and pathogens that activated both the Vα3S1/Vβ13S1 TCR and CD8+ T cells from psoriasis patients. Using fluorescent HLA-C*06:02 tetramers loaded with ADAMTSL5 or wheat peptides, we find that the same CD8+ T cells may recognize both autoantigen and environmental antigens. A wheat-free diet could alleviate psoriasis in several patients.DiscussionOur results show that due to TCR polyspecificity, several environmental antigens corresponding to previously suspected psoriasis risk conditions converge in the reactivity of a pathogenic psoriatic TCR and might thus be able to stimulate the psoriatic autoimmune response against melanocytes. Avoiding the corresponding environmental risk factors could contribute to the management of psoriasis.